Foundations of XML processing : the tree-automata approach - Hosoya, Haruo , 1972- (Cambridge University Press, 2011)
"This is the first book to provide a solid theoretical account of the foundation of the popular data format XML. Part I establishes basic concepts, starting with schemas, tree automata, and pattern matching and concluding with static type checking for XML as a highlight of the book. In Part II the author turns his attention to more advanced topics, including efficient "on-the-fly" tree automata algorithms, path- and logic-based queries, tree transformation, and exact type checking. Many examples of code fragments illustrate XML features, and exercises are provided to enhance understanding. Thus the book should be very useful both for students and for XML researchers"-- Provided by publisher